The Effect of Learning Media in Pandemic Times on Education - Runi Fazalani; Fitriyah Fitriyah; Ida Bagus Benny Surya Adi Pramana; Eka Adnan Agung; Tamsik Udin (Budapest International Research and Critics University, 2022)
Media as a component in a learning system has a very important position in the learning process. Therefore, the purpose of this study was to determine the effect of learning media in improving the quality of learning. The research method is the research method used by the researcher is an experimental method with a pre-experimental design. Researchers used a quantitative approach. The experimental method in this study was used to measure the changes that occurred after the treatment. The result of this study is that the influence of learning media during the COVID-19 pandemic has proven to be effective in increasing student learning outcomes.